Oberonia acaulis Griff. var. latipetala (Orchidaceae) - A new variety from Manipur, India (Bangladesh Journal of Plant Taxonomy, 2014)
Not availableDOI: http://dx.doi.org/10.3329/bjpt.v21i1.19273Bangladesh J. Plant Taxon. 21(1): 93-95, 2014 (June)